Venue-based versus Geosocial Networking Application-based Recruitment of Young Men Who Have Sex with Men: An Examination of Feasibility. Issue 2 (May 2022) - Gibbs, Jeremy J.; Traube, Dorian E.; Goldbach, Jeremy T.
Because of the high cost, venue-based probability sampling of young men who have sex with men (YMSM) is largely inaccessible to social researchers. The aim of this study is to compare the feasibility of implementing geosocial networking application-based (GSNA) and venue-based prob`ability sampling of young men who have sex with men. A cross-sectional survey conducted in Los Angeles in 2017 and 2018 recruited 124 YMSM using both methods. We compared costs and hours of work for each method. Per participant, GSNA-based methods cost approximately 157 USD compared to 383 USD for the venue-based methods. For sample sizes up to 1, 000, venue-based methods cost over two times more than GSNA-based methods. Findings indicate that research teams with limited resources may be able to implement probability-based recruitment by using GSNA. By lowering the cost of research and maintaining probability-based methodological rigor, GSNAs can increase the amount of social research with YMSM.